Pengaruh Bentuk Lansekap Terhadap Kebisingan Masjid Baitussalihin Ulee Kareng Kota Banda Aceh - Rifal Alfayed; Hadi Kurniawan; Zia Faizurrahmany El Faridy (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
The mosque building was designed taking into account the need for quiet and low noise levels to support Muslim worship. This research aims to analyze the acoustic comfort of the Baitussalihin Ulee Kareng Mosque, Banda Aceh City. This research uses qualitative and quantitative methods (Mixed Methods). Observations began with measuring the background noise level and absorption coefficient using a sound level meter. Interview data was collected in a semi-structured manner using an interview guide for visitors to the Baitussalihin Ulee Kareng Mosque. The data analysis technique used is descriptive technique.